Subsurface monitoring of large rockslides in norway: a key requirement for early warning - Blikra, Lars H.; Kristensen, Lene; Lovisolo, Mario (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value="{"1":2,"2":"The risk posed by large rockslides in Norway is due to long run-out, the possibilities for river damming and the generation of disastrous tsunamis in fjords. The investigations, monitoring and earlywarning that have been designed and implemented for the Norwegian rockslides follows strong requirements guided in national codes. Extensive investigations and implementation of relatively dense sensor network is needed in order to achieve reliable and robust monitoring of large and complex rockslides. The Norwegian codes have strong and specific requirements for using early-warning to reduce risk. The need of gaining sufficient knowledge is especially important for the operative handling of the total early-warning systems. Subsurface borehole logging and instrumentation is a mandatory part of the requirements. A real-time instrumentation with a continuous coverage from the surface and down to potential sliding planes of the rockslides is implemented for the Norwegian examples. These example shows that the multiparametric borehole probe DMS used in these cases can be regarded as a geotechnical lab within the rockslide, and gives in detail crucial data about deformations, water-pressure and temperatures at the active zone. This are considered to be critical data during an acceleration phase."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">The risk posed by large rockslides in Norway is due to long run-out, the possibilities for river damming and the generation of disastrous tsunamis in fjords. The investigations, monitoring and earlywarning that have been designed and implemented for the Norwegian rockslides follows strong requirements guided in national codes. Extensive investigations and implementation of relatively dense sensor network is needed in order to achieve reliable and robust monitoring of large and complex rockslides. The Norwegian codes have strong and specific requirements for using early-warning to reduce risk. The need of gaining sufficient knowledge is especially important for the operative handling of the total early-warning systems. Subsurface borehole logging and instrumentation is a mandatory part of the requirements. A real-time instrumentation with a continuous coverage from the surface and down to potential sliding planes of the rockslides is implemented for the Norwegian examples. These example shows that the multiparametric borehole probe DMS used in these cases can be regarded as a geotechnical lab within the rockslide, and gives in detail crucial data about deformations, water-pressure and temperatures at the active zone. This are considered to be critical data during an acceleration phase.